Modelling the extreme precipitation event over Madeira Island on 20 February 2010 - Luna, T. (2019)
In the morning of the 20 February of 2010 an extreme precipitation event occurred over Madeira Island. This event triggered several ﬂash ﬂoods and mudslides in the southern parts of the island, resulting in 42 conﬁrmed deaths, 100 injured, and at least 8 people still missing. These extreme weather conditions were associated to a weather frontal system moving northeastwards embedded in a low pressure area centered in the Azores archipelago. This storm was one in a series of such storms that affected Portugal, Spain, Morocco and the Canary islands causing ﬂooding and strong winds. These storms were bolstered by an unusually strong sea surface temperature gradient across the Atlantic Ocean. In this study, the WRF model is used to evaluate the intensity and predictability of this precipitation extreme event over the island. The synoptic/orographic nature of the precipitation is also evaluated, as well as the sensitivity of the model to horizontal resolution and cumulus parameterization. Orography was found to be the main factor explaining the occurrence, amplitude and phase of precipitation over the Island.